Kombinasi Metode Rank Order Centroid dan Complex Proportional Assessment Dalam Pemilihan Jasa Kontruksi Perbaikan Gedung - Sabandar, Vederico Pitsalitz (Journal of Data Science and Information Systems, 2024)
Building refurbishment is a process that involves restoring, maintaining, or improving the physical condition of a building so that it can function optimally and safely. The purpose of building refurbishment is to extend the service life of the building, improve user comfort and safety, and maintain the aesthetic value and investment value of the property. One common problem is the inability of contractors to complete projects according to the expected standards or within the set time limit. In addition, lack of transparency in bidding, unexpected additional costs, and lack of communication between the building owner and the contractor can also be obstacles. The combination of ROC and COPRAS weighting methods allows users to benefit from both approaches. ROC provides flexibility in determining the weight of criteria based on user preferences, while COPRAS makes it possible to handle the complexity of the relationship between criteria and alternatives. By combining the two, users can optimize the decision-making process by taking into account various relevant aspects in the evaluation of alternatives. This provides a solid foundation for assessing the relative performance of each alternative comprehensively and efficiently. The results of recommendations in the selection of building repair construction services ranked first with a value of 100% obtained by PT BPS construction services, ranked second with a value of 93.63% obtained by PT HRB construction services, ranked third with a value of 93.68% obtained by PT SKL construction services. Based on these results, it becomes a recommendation for companies to make more informed and precise decisions in selecting construction services for building repair projects.